Between nostalgia and melancholy: notes about a pasillo and its significance in the symbolic construction of a community - Robles, Humberto E. (2012)
The author examines “Manabí”, an Ecuadorian “pasillo”, with the purpose of underlining the various components that a popular song can have on the symbolic creation of the social imaginary of a community. Among the features he studies are: place of origin, history, the presence of collective and family mores, the national repertoire of songs and their function in the creation of local identities, all elements that contribute to the presence of the “burden” of tradition. A burden evident in the tension that ensues between the regional and what lies beyond not only in “Manabí” (Elías Cedeño Jerves’ homage to his native province), but also on continental horizons (López Velarde, Borges, Rulfo). The author concludes with a critical reading of “Manabí” in which he highlights the fruitless isolation that often ensues from the despair –within and in the social context– caused by exile, by the tension between nostalgia and melancholy, between tradition and yearnings.